Seismic performance evaluation and strengthening proposal for a reconstruction project of a historic masonry building demolished in the 1940s. (1st May 2023) - Uzdil, Oguz; Cosgun, Turgay; Sayin, Baris; Akcay, Cemil
Abstract: For heritage structures demolished or disappeared over the years, reconstruction projects are prepared based on the original architecture and structural characteristics. Before reconstruction of historic buildings, which represent construction techniques and material characteristics of their era, assessing seismic performance is very important. Otherwise, these valuable heritage buildings may pose a risk of earthquake-induced collapse. However, this important procedure is mostly overlooked in reconstruction practices. Accordingly, the current paper presents a seismic evaluation of a reconstruction project for a historic masonry building built in 1866 and was later demolished in the 1940s. Linear, nonlinear, and kinematic limit analyses were conducted. The seismic performance was determined by comparing the shear force and inter-story drifts as well as overturning and bending behaviors with the limit values given in the code. As the seismic performance level was found to be inadequate, a strengthening proposal was made. It is believed that the evaluation methodology including global and local analyses as well as the strengthening technique presented in the current study would make a valuable contribution to the literature on the reconstruction of disappeared or demolished buildings based on the original construction technique and materials. Highlights: This paper focuses on a historic masonry building built in 1866 and was later demolished in the 1940s. Seismic performance analyses are performed for the proposed reconstruction model. Linear, nonlinear, and kinematic limit analyses were conducted. A strengthening technique is proposed for the reconstruction model.